Anticipatory grief in family members and patients under palliative care: An integrative review (Research, Society and Development, 2025)
This work proposes to reflect on Anticipatory Grief (AG) experienced by family members and patients in terminal illness situations. An integrative review was conducted. For the bibliographic research, a survey was carried out in three databases: PubMed, LILACS, and SciELO. The descriptors used were standardized based on the DeCS website. The inclusion criteria included the availability of the full text in Portuguese, English, or Spanish, published within the timeframe of 2020 to 2025. Articles not available in full, or in a language other than those mentioned above, or published before the year 2020 were excluded. Four articles met the proposed criteria. Anticipatory Grief is distinguished from post-mortem grief by involving emotional, cognitive, and behavioral responses to the proximity of the predicted loss, manifesting as an ambiguous loss. The experience of AG by family caregivers carries a dichotomy, potentially being a source of overload, but also being seen as a moment of learning and sharing. There are indications that the AG of family members is often not addressed by health teams, suggesting an invisibility of the suffering. Thus, it is concluded that AG is a complex phenomenon, a psychological reaction that begins before the actual death in situations of impending finitude, such as terminal illnesses and dementias. Because it generates great suffering, AG is considered clinically relevant, as it is a strong predictor of complicated grief after the actual death, requiring specialized psychological intervention for its management.